Introduccion de germoplasma tropical en la mejora de maiz forrajero - Casañas, F.=700 1 Bosch, L.; Sanchez, E.; Ferret, A.; Plaixats, J.; Albanell, E.
(Es, En)
ilus., 23 ref.
Keywords: MEJORA GENETICA; GRAMINEAS FORRAJERAS; ZEA MAYS; HIBRIDOS; ESPAÑA